Role Playing Reveals Student Communication and Collaborative Interaction in IPAS: Role Playing Mengungkap Komunikasi dan Interaksi Kolaboratif Siswa dalam IPAS - Suciati, Enggar; Sari, Nurratri Kurnia (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Communication skills are a core component of 21st-century learning, particularly in integrated Natural and Social Sciences (IPAS), where students are required to actively express ideas and engage in social interaction. Specific Background: Role-playing is applied as an active learning strategy to facilitate communication practice among grade IV students in IPAS learning contexts. Knowledge Gap: Previous studies primarily emphasize general communication outcomes using quantitative approaches, while detailed qualitative exploration of communication processes and indicators remains limited. Aims: This study aims to explore students’ communication skills through role-playing activities in IPAS learning. Results: Using a descriptive qualitative design involving 22 students, findings indicate that most students demonstrate clear pronunciation (90.91%) and fluency (86.36%), alongside increased confidence, appropriate gestures, and improved mastery of subject content. Students also begin to utilize facial expressions, eye contact, and collaborative interaction during group activities. Novelty: The study identifies the emergence of collaborative communication through group discussion, role distribution, and peer feedback, extending beyond traditional communication indicators. Implications: These findings suggest that role-playing supports holistic communication development, integrating verbal, nonverbal, affective, and social dimensions, and provides a practical strategy for fostering interactive and meaningful IPAS learning. Highlights• High clarity and fluency observed in student dialogue performance• Group interaction fosters peer feedback and shared understanding• Learning activities integrate conceptual mastery with expressive behavior KeywordsStudent Communication; Role Playing Method; IPAS Learning; Collaborative Communication; Elementary Education